Research perspectives on paddy field systems: ecological functions and environmental impacts - Yanhua Zhuang; Hongbin Liu; Liang Zhang; Sisi Li (International Journal of Agricultural Sustainability, 2020)
Paddy is an important artificial wetland ecosystem related to sustainable development of agriculture and environment. According to 12,276 paddy-related publications in SCIE database during 1997–2016, this study revealed the global paddy research trends. The paddy research experienced an exponential growth. This research had remarkable regional characteristic and was mainly distributed across Asia, Western and Central Europe and Northern America. The rice production and accompanied environmental issues were main driving factor to promote paddy research. A group of developing countries led by China and India played important role in global paddy research. China was the largest contributor with rapid development after 2009, followed by Japan, the USA and India. The focus of paddy research has extended from rice yield to food security and environmental issues. Paddy wetland ecosystem and biodiversity, greenhouse gas emission and climate change, heavy metal pollution and food security, nutrient loss and water quality were research hotspots; the increasing use of RS, GIS and models promoted the extension of paddy research from field- to regional and global scale; field management measures, such as water management and biochar, were applied to improve environment issues. Ecological function and environmental impacts will be the primary targets of future paddy research.